THE INFLUENCE OF USING ENGLISH SONGS ON THE STUDENTS’ ACHIEVEMENT IN PRONOUNCING ENGLISH WORDS - Ridhayatullah Ridhayatullah; Usman Kasim; Bukhari Daud (English Education Journal, 2020)
This research aimed at identifying the influence of using English songs on students’ achievement in pronouncing English words at SMP Islam Cendekia Aceh Besar Academic Year 2018/2019. The population of this research was all VII Grade students. The sample of the research was divided into 31 students of the experimental group and 32 students of the control group. The experimental group was taught by using English songs technique while the control group was not taught by using English songs. This research was experimental research, under quasi experimental research. The data were taken from an oral test method or sound of production and questionnaire which were given in the learning process. The result of the research shows that the English songs technique can influence the students’ achievement in pronouncing English words. It is concluded from the post-test that there was a statistical difference in the mean score between the experimental and control group. The mean score of the experimental group was 81.51 and the mean score of the control group was 60.37. It means that the mean score of the experimental group is higher than the control group. Moreover, the result of z-test indicated that the students taught by using an English song had a better improvement in English word pronunciation in which z-score (9.05) was higher than the critical value (1.96). It could be concluded that English song strategy effectively improved students’ achievement in pronouncing English words.